Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Feminist Debates about Women and National Socialism - Grossmann, Atina (Gender & History, 1991)
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; cours; discipline; europe; fascisme; his4830; histoire; histoire des femmes*; histoire et politique; historiographie; holocauste; maternité; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; thématiques; violences; violences contre les femmes*; violences d'état; violences sexuelles

Idola Saint-Jean et le radicalisme féministe de l’entre-deux-guerres - Lamoureux, Diane (Recherches féministes, 1991)
Les suffragistes nous semblent souvent de bonnes bourgeoises aux méthodes et aux idées surannées. Pourtant, le féminisme de l'entre-deux-guerres est aussi diversifié que le féminisme actuel. Il est utile d'analyser ce passé féministe dans le contexte du mouvement de réforme sociale de l'époque pour ensuite apprécier le radicalisme de la pensée politique d'Idola Saint-Jean, une pensée politique marquée au coin de la justice sociale, de la démocratie et d'un sens aigu de l'antagonisme entre les sexes qui conditionne son activité militante
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; discipline; droit de vote; droits des femmes*; histoire et politique; justice sociale; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; suffragettes; thématiques

L'épopée du suffrage féminin au Québec (1920-1940) - Darsigny, Maryse (Service aux collectivités de l'UQAM, 1990)
Perte et reconquête du droit de vote des femmes. La structuration du mouvement pour le suffrage féminin au Québec. Les réactions contre le suffrage féminin. Les suffragettes persistent. L'année historique pour les Québécoises.
https://biblio.cdeacf.ca/cgi-bin/koha/opac-detail.pl?biblionumber=202897
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; SAC; amériques; droit de vote; droits des femmes*; histoire et politique; périodes historiques; québec; régions géographiques; suffragettes; thématiques